Heart Rate Variability Analysis in Episodic Migraine: A Cross-Sectional Study - Zhang, Lvming; Qiu, Shi; Zhao, Chunxia; Wang, Peifu; Yu, Shengyuan (Frontiers in Neurology, 2021)
Objective: It has been reported that autonomic nervous dysfunction is more prevalent in migraineurs. Heart rate variability (HRV) is a commonly used method to evaluate the autonomic nervous function modulation. However, HRV changes in migraine are still contradictory. The main aim of this study was to explore the potential HRV change patterns in episodic migraine (EM), and whether there were differences in HRV between EM headache period and the interval period. Patients and Methods: We conducted a cross-sectional study including eighteen patients with EM and twelve age- and sex-matched controls. The characteristics of demographics, some lifestyle factors and psychological conditions were assessed at baseline. HRV analyses including time domain and frequency domain analysis were recorded not only in headache interval period but also in the headache attack period. Results: HRV time domain parameter triangle index was significantly lower in the patients with migraine interval period than controls (23.33 ± 7.76 vs.16.44 ± 10.29, P=0.002). The time domain parameter the heart rate variability standard deviation of all NN intervals in 24 hours (SDNN) was much lower in the headache attack period than migraine interval period in EM (56.94 ± 22.09 vs. 115.94 ± 46.88, p<0.001). All the HRV parameters showed a decreased trend in migraine attack period than controls. However, the frequency domain parameters including high-frequency power (HF), low-frequency power (LF) and very low-frequency power (VLF) in patients with migraine did not differ from the control group significantly. Conclusions: The present cross-sectional study suggests that EM has an autonomic nervous dysfunction with a much lower time domain analysis. This HRV change pattern is more significant in the migraine headache period. Maybe larger prospective cohort studies are warranted to validate these findings.